2020
DOI: 10.1093/jamia/ocaa220
|View full text |Cite
|
Sign up to set email alerts
|

Development of a predictive model for retention in HIV care using natural language processing of clinical notes

Abstract: Objective Adherence to a treatment plan from HIV-positive patients is necessary to decrease their mortality and improve their quality of life, however some patients display poor appointment adherence and become lost to follow-up (LTFU). We applied natural language processing (NLP) to analyze indications towards or against LTFU in HIV-positive patients’ notes. Materials and Methods Unstructured lemmatized notes were labeled wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Afshar et al [31] used NLP of clinical notes to identify patients with alcohol misuse, demonstrating greater accuracy than EMR-based billing codes; however, this study was performed among hospitalized trauma patients rather than with outpatients living with HIV. Oliwa et al [32] used NLP of clinical notes to identify phrases associated with improved engagement in HIV care. Their study identified NLP phrases related to substance use and mental health among people living with HIV, but they did not compare their findings with documentation in structured EMR fields.…”
Section: Introductionmentioning
confidence: 99%
“…Afshar et al [31] used NLP of clinical notes to identify patients with alcohol misuse, demonstrating greater accuracy than EMR-based billing codes; however, this study was performed among hospitalized trauma patients rather than with outpatients living with HIV. Oliwa et al [32] used NLP of clinical notes to identify phrases associated with improved engagement in HIV care. Their study identified NLP phrases related to substance use and mental health among people living with HIV, but they did not compare their findings with documentation in structured EMR fields.…”
Section: Introductionmentioning
confidence: 99%
“…• Oliwa et al [41] devised a system to analyze the presence or absence of lost to follow-up (LTFU) practices by HIV-positive patients. This is necessary because the poor response to appointments may negatively affect the patient's mortality and decrease their quality of life.…”
Section: Miscellaneous Practicesmentioning
confidence: 99%
“…ARDSFlag uses machine learning (ML) and natural language processing (NLP) techniques to evaluate Berlin criteria. ML and NLP have been proven to offer strong potential for identifying and predicting complex medical conditions by incorporating EHR data [14][15][16][17] . We also develop a visualization that integrates all components of the Berlin criteria in one graph.…”
Section: Introductionmentioning
confidence: 99%